THE DISTRICT INTEGRATED ADMINISTRATION SERVICES QUALITY (PATEN), SIDOARJO, SIDOARJO REGENCY - Alfiyanti, Nurin; Mursyidah, Lailul (ANTIS PUBLISHER, 2024)
General Background: Good public service is a core characteristic of good governance. Innovations such as the Sub-district Integrated Administration Services (PATEN) have been introduced to improve public service quality at the sub-district level. Specific Background: The implementation of PATEN at the Sidoarjo Sub-district Office, Sidoarjo District, aims to streamline administrative services and enhance community satisfaction. Knowledge Gap: Despite the PATEN initiative, challenges remain in service efficiency and quality, particularly in ensuring reliability, responsiveness, and time guarantees. Aims: This research analyzes the quality of integrated administrative services (PATEN) at the Sidoarjo Sub-district Office using a qualitative, descriptive approach. Results: Based on the service quality theory by Zeithaml, Parasuraman, and Berry, the study evaluates five indicators: tangibles, reliability, responsiveness, assurance, and empathy. Tangibles are sufficient, with adequate infrastructure. Reliability is ensured through competent employees and SOP adherence. Responsiveness shows employees serve the community well, though time guarantees, particularly for KTP issuance, need optimization due to data verification delays and limited resources. Empathy is reflected in equitable service delivery without discrimination. Novelty: The research highlights the importance of optimizing time guarantees and resource availability to improve PATEN implementation in Sidoarjo. Implications: This study provides insights for local government to enhance service delivery by addressing existing challenges and ensuring more responsive, reliable, and efficient administrative services.